Analysis of Vendors’ Ability to Purchase Stalls After Revitalization: A Case Study of “Pasar Akik” Sukaramai, Medan City - Yuda Mahendra Hasibuan; Sugianto (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The revitalization of traditional markets is one of the government's strategies to enhance the competitiveness of the informal sector amid the growing dominance of modern markets. However, in practice, revitalization does not always generate positive impacts for all market stakeholders. This article examines the social and economic dynamics experienced by traders and consumers at Pasar Akik, Medan, following its revitalization. Using a qualitative approach with observation and in-depth interview techniques, the study found that increased stall rental prices and the reduction in trading space size were the main issues raised by traders. These conditions have led to rising product prices, which in turn have affected consumer behavior and reduced the number of buyers. Although the market now appears cleaner and more organized physically, the revitalization is perceived to have yet to deliver economic justice for small-scale traders. This study recommends the need for policies that integrate physical, social, and economic aspects to ensure that the revitalization process does not create new forms of inequality. These findings are expected to provide input for local governments, market managers, and academics in designing a more inclusive and sustainable model for public market revitalization.